Serving Sci-Tech Library Users With Disabilities - Coonin, Bryna (East Carolina University, 2001)
Service to library users with disabilities has been the subject of numerous books, articles, and presentations, but it is useful to consider this issue specifically in the context of science libraries for several reasons. In the United States we acknowledge an established need for scientists, but have long overlooked the pool of scientific interest and talent among individuals with disabilities. Sci-tech librarians can play a significant role in the encouragement of scientific talent among library users with disabilities by making the library environment accessible and ensuring as much as possible the independent access to information that is so critical to scientific endeavor. Some of the specific ways librarians in sci-tech libraries can contribute to an accessible electronic library environment include developing basic familiarity with relevant assistive technologies, creating accessible web pages, monitoring accessibility of electronic databases purchased for the library, and by preparing accessible bibliographic instructional activities.
Keywords: Users with disabilities; Science librarians